MUDANÇAS CLIMÁTICAS AMEAÇAM A DISTRIBUIÇÃO POTENCIAL DE UMA ESPÉCIE ARBÓREA NATIVA DA MATA ATLÂNTICA - Fernanda Gomes, Paula; Eduarda Gomes Fernandes , Maria; Francisca Gomes Silva, Ana; Bailly , Dayani; Cristina de Paula Souza, Beatriz; Flávia Batista Silva, Valéria (ANAIS DO ENIC, 2026)
-